VD_FINDINFO HC / 2012 / 352 vom 3. April 2012 - VD Tribunal cantonal (2012)
MESURE PROVISIONNELLE, ARCHITECTE, HONORAIRES, COMPÉTENCE | 82 CO, 62 al. 1 LDA, 62 al. 1bis LDA, 65 LDA, 74 al. 3 LOJV, 13 CPC (CH), 261 al. 1 CPC (CH), 262 CPC (CH), 308 al. 1 let. b CPC (CH), 308 al. 2 CPC (CH), 31 CPC (CH), 310 CPC (CH), 5 al. 1 let. a CPC (CH), 5 al. 2 CPC (CH), 58 al. 1 CPC (CH), 90 CPC (CH), 47 al. 4 CDPJ